Dynamic modeling and simulation of CO2 chemical absorption process for coal- fired power plants - Lawal, Adekola; Wang, Meihong; Yeung, Hoi; Stephenson, Peter (Cranfield University, 2009)
Post combustion capture via chemical absorption is viewed as the most mature CO capture technique. The effects of the addition of CO chemical absorption process on power plant performance have been studied using various steady-state models. However, there are several gaps in the understanding of the impact of post combustion capture on the operability of the power plant. These questions could be addressed by studying the dynamic behavior of such plants. In this study, dynamic models of the CO chemical absorption process were developed and validated. Dynamic analyses of the process reveal that absorber performance is sensitive to L/G ratio and that changes in reboiler duty significantly affect the regenerator performance.